2014
DOI: 10.1186/1751-0759-8-19
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel, short, self-completed questionnaire on empowerment for patients with type 2 diabetes mellitus and an analysis of factors affecting patient empowerment

Abstract: BackgroundPatient empowerment has recently been proposed as an important concept in self-management for effective glycemic control. A concise self-completed questionnaire for patients with type 2 diabetes mellitus was created to comprehensively evaluate their empowerment on the basis of self-managed dietary/exercise behaviors, psychological impact, and family support. The reliability and validity of this short questionnaire were tested and factors relating to patient empowerment were analyzed.MethodsThe self-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 15 publications
5
15
1
Order By: Relevance
“…Previous studies have found that men evidence higher empowerment levels than women [26]. A study of empowerment in diabetes patients also found a significant effect of gender where female patients may be struggling with greater psychological or family communication problems than males [27]. We also found that with increasing age, empowerment scores increased on both factors.…”
Section: Discussionsupporting
confidence: 74%
“…Previous studies have found that men evidence higher empowerment levels than women [26]. A study of empowerment in diabetes patients also found a significant effect of gender where female patients may be struggling with greater psychological or family communication problems than males [27]. We also found that with increasing age, empowerment scores increased on both factors.…”
Section: Discussionsupporting
confidence: 74%
“…The associated factors of self‐management in our study differ from those of Alrahbi (), Hara et al (), D'Souza et al () and Lin et al (). We found no significant relationship between diabetes self‐management and glycaemic control, similar to the study of Alrahbi ().…”
Section: Discussioncontrasting
confidence: 99%
“…The associated factors of self‐management in this study are the same as those of Alrahbi () and Hara et al (), who noted that gender was related to self‐management. In addition, male self‐efficacy is better than that of females, and males have better health behaviours (Burner, Menchine, Taylor, & Arora, ).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The Diabetes Empowerment Scale (DES) has shown sufficient internal consistency, construct validity, reproducibility, factorial construct validity, and concurrent validity among patients with type 2 diabetes [9]. The results of the DES correlate with age, level of education, disease duration, educational program of diabetes applied, and metabolic control [10, 11].…”
Section: Methodology Of Empowerment Therapymentioning
confidence: 99%